COVID-19: an 'extraterrestrial' disease?. (September 2021) - Paul, Elisabeth; Brown, Garrett W.; Dechamps, Mélanie; Kalk, Andreas; Laterre, Pierre-François; Rentier, Bernard; Ridde, Valéry; Zizi, Martin
Highlights: The COVID-19 response should no longer be considered an exceptional task It should be managed following long-proven principles of medicine and public health A complex zoonotic disease cannot be solved through a magic bullet cure or vaccine Disease heterogeneity requires targeted measures and reduction of comorbidities The response should also mitigate the risk of transition from infection to disease Abstract: Background: Since the beginning of the pandemic, COVID-19 has been regarded as an exceptional disease. Control measures have exclusively focused on 'the virus', while failing to account for other biological and social factors that determine severe forms of the disease. Aim: We argue that although COVID-19 was initially considered a new challenge, justifying extraordinary response measures, this situation has changed — and so should our response. Main arguments: We now know that COVID-19 shares many features of common infectious respiratory diseases, and can now ascertain that SARS-CoV-2 has not suddenly presented new problems. Instead, it has exposed and exacerbated existing problems in health systems and the underlying health of the population. COVID-19 is evidently not an 'extraterrestrial' disease. It is a complex zoonotic disease, and it needs to be managed as such, following long-proven principles of medicine and public health. Conclusion: A complex disease cannot be solved through a simple, magic-bullet cure or vaccine. The heterogeneity of population profiles susceptible to developing a severe form of COVID-19 suggests the need to adopt varying, targeted measures that are able to address risk profiles in an appropriate way. The critical role of comorbidities in disease severity calls for short-term, virus-targeted interventions to be complemented with medium-term policies aimed at reducing the burden of comorbidities, as well as mitigating the risk of transition from infection to disease. Strategies required include upstream prevention, early treatment, and consolidation of the health system.